Fatal melioidosis in a captive elephant trunk snake (Acrochordus javanicus) in Kuala Lumpur, Malaysia - Sadiq, Muhammad Abubakar; Hassan, Latiffah; Zakaria, Z.; Saharee, Abdul Aziz; Abba, Yusuf (Veterinary Association Malaysia, 2016)
An adult female Elephant Trunk Snake (Acrochordus javanicus) was reported to have been weak and inappetent for five days. The following morning the snake found dead, while in the process of shedding its skin. On post mortem examination, there were multiple circumscribed caseous nodules of various sizes distributed all over the liver, along the respiratory tract and on the lungs. Bacteriological analysis of the lungs and liver swab samples yielded Burkholderia pseudomallei, which was confirmed by PCR amplification of specific 16S rRNA. The condition was diagnosed as melioidosis and the organism was genotypically characterized as sequence type 51, a genotype that has been previously characterized in humans in Malaysia. Antibiotic susceptibility by both Disc diffusion or Kirby Bauer and E-test minimum inhibitory concentration (MIC) showed that the organism exhibited susceptibility to meropenem, imipenem, ceftazidime, cotrimoxazole and co-amoxyclav; the antibiotics recommended in the treatment of melioidosis.